The Relation between of the Management and the Efficient Development of Domestic Water Transportation in the Midland of Thailand - Thanasottigulanun, Sitthapawee; Santisan, Burin; Pisitkasem, Phat (WMS Journal of Management, 2020)
The objectives of this study were to study 1) the level of management of Domestic Water Transportation and 2) the relation between management and the efficient development in the Domestic Water Transportation in the midland of Thailand. This research is a mixed method using quantitative and supplemented with qualitative research. The quantitative method used the questionnaire to collect 225 samples which were collected from 65 companies listed from the Marine Department in 2014. The statistical techniques were utilized to analyze data including mean, standard deviation and Pearson’s Correlation Coefficient. The research also used qualitative research data, collected by interviewing informants such as entrepreneurs, government officials and experts, to support results from the Quantitative research results and to be in line with the current operational situation. The results showed that the overall mean score of the management was 4.13, a high level. The Strategic management had the highest score of mean (Mean = 4.37) and the lowest (Mean = 3.71) belonged to the Customer Relationship Management. All 8 factors were statistically significant level of .01. Pearson’s Correlation Coefficient was as follows: Motivation (r = 0.768), Communication (r=0.704) Participation (r = 0.606) Knowledge Management (r = 0.565) Corporate Social Responsibility (r = 0.546) Strategic management (r = 0.538) Customer Relationship Management (r = 0.351) และ Human Resource Management (r = 0.328).